Penerapan Sistem Pembelajaran Pada Tingkat Pendidikan MDTA di MDTA Al Khairat Tembung - Fazli Abdillah; Chandra Winata; Indah Wahyuni; Zoe Zarka Syafiq (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The aim of this research is to find out how the Learning System is implemented at the MDTA Education Level at MDTA Al Khairat Tembung. The method in this research is a qualitative method through data collection through interviews with one of the sources as an instrument. The informant in this research was one of the madrasa heads at MDTA Al Khairat Tembung and took a review of several journal and book literature. Data collection techniques use 3 methods, namely interviews, observation and documentation. The research results show that the implementation of the learning system cannot be separated from the obstacles or problems faced, such as the lack of a madarasah budget to meet various needs such as operational costs, school facilities and infrastructure, teacher salaries, and procurement of subject books.